2009
DOI: 10.1016/j.clinbiomech.2008.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Differences in lumbopelvic motion between people with and people without low back pain during two lower limb movement tests

Abstract: Background-Clinical data suggest that active limb movements may be associated with early lumbopelvic motion and increased symptoms in people with low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
150
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(162 citation statements)
references
References 34 publications
5
150
1
6
Order By: Relevance
“…Previously, one study on the lumbar spine found greater lumbopelvic motion in the transverse plane during lower limb movements of LBP patients [14]. The study suggested the need to understand the dynamic coordination of the lumbopelvic region during other functional activities.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previously, one study on the lumbar spine found greater lumbopelvic motion in the transverse plane during lower limb movements of LBP patients [14]. The study suggested the need to understand the dynamic coordination of the lumbopelvic region during other functional activities.…”
Section: Discussionmentioning
confidence: 92%
“…There are several reports utilizing motion analysis for subjects with and without LBP with regard to interactions with the lower extremities [13][14][15]. As Bouisset initially proposed, stabilization of the pelvis and trunk is necessary for all movements of the upper and lower extremities [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-specific LBP comprises a large proportion of LBP cases, and the cost of treating LBP is high [3][4][5]. Several studies have demonstrated factors contributing to the development of LBP, and LBP patients present with various symptoms or behaviors [6][7][8]. For this reason, clinicians and investigators have sought to determine sources and/or causes of LBP based on posture and movement tests, and to provide guidelines for the management of LBP [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies of lumbopelvic motion have been conducted through kinematic investigation into LBP; however, no reported study has examined the effects of limited hip flexion on lumbopelvic motion in LBP during hip flexion in sitting [2,4,7,19]. A kinematic study of lumbopelvic motion may be helpful in understanding altered movement strategies in subjects with LBP accompanying limited hip flexion during seated hip flexion.…”
Section: Introductionmentioning
confidence: 99%